Myxedema madness complicating postoperative follow-up of thyroid cancer - Yanina J. Morosán Allo; Melanie Rosmarin; Agustina Urrutia; Maria Cristina Faingold; Carla Musso; Gabriela Brenta (Archives of Endocrinology and Metabolism)
Although hypothyroidism is associated with an increased prevalence of psychiatric manifestations, myxedema madness is rarely observed. We report the case of a 62-year-old woman with no prior history of psychiatric disorders, who presented to the emergency department with psychomotor agitation 6 weeks after total thyroidectomy for papillary thyroid cancer. Serum thyroid stimulating hormone (TSH) on admission was 62.9 mIU/L and free T4 was < 0.35 ng/dL, indicating severe hypothyroidism. After ruling out other possible causes, the diagnosis of myxedema madness was considered; hence, antipsychotic drug treatment and intravenous levothyroxine were prescribed. Behavioral symptoms returned to normal within 4 days of presentation, while levels of thyroid hormones attained normal values 1 week after admission. Recombinant TSH (Thyrogen®) was used successfully to prevent new episodes of mania due to thyroid hormone withdrawal in further controls for her thyroid cancer. This case illustrates that myxedema madness can occur in the setting of acute hypothyroidism, completely reverting with levothyroxine and antipsychotic treatment. Recombinant TSH may be a useful tool to prevent myxedema madness or any severe manifestation of levothyroxine withdrawal for the follow-up of thyroid cancer.